Increasing cardiac pyruvate dehydrogenase flux during chronic hypoxia improves acute hypoxic tolerance - Handzlik, Michal; Constantin-Teodosiu, Dumitru; Greenhaff, Paul L.; Cole, Mark (Wiley, 2018)
The pattern of metabolic reprogramming in chronic hypoxia shares similarities with that following myocardial infarction or hypertrophy, however the response of the chronically hypoxic heart to subsequent acute injury, and the role of metabolism is not well understood. Here, we determined the myocardial tolerance of the chronically hypoxic heart to subsequent acute injury, and hypothesised that activation of a key regulator of myocardial metabolism, the pyruvate dehydrogenase complex (PDC), could improve hypoxic tolerance. Mouse hearts, perfused in Langendorff mode, were exposed to 30min of hypoxia, and lost 80% of prehypoxic function (p=0.001), with only 27% recovery of pre-hypoxic function with 30min of re-oxygenation (p=0.046). Activation of the PDC with infusion of 1mM dicholorocacetate (DCA) during hypoxia and re-oxygenation did not alter function. Acute hypoxic tolerance was assessed in hearts of mice housed in hypoxia for 3wks. Chronic hypoxia reduced cardiac tolerance to subsequent acute hypoxia, with recovery of function 22% of pre-acute hypoxic levels, vs 39% in normoxic control hearts (p=0.012). DCA feeding in chronic hypoxia (per os, 70mg/kg/day) doubled cardiac acetylcarnitine content, and this fell following acute hypoxia. This acetylcarnitine use maintained cardiac ATP and glycogen content during acute hypoxia, with hypoxic tolerance normalised. In summary, chronic hypoxia renders the heart more susceptible to acute hypoxic injury, which can be improved by activation of the PDC and pooling of acetylcarnitine. This is the first study showing functional improvement of the chronically hypoxic heart with activation of the PDC, and offers therapeutic potential in cardiac disease with a hypoxic component.